Tumor induces muscle wasting in mice through releasing extracellular Hsp70 and Hsp90 - Guohua Zhang (Nature Portfolio, 2017)
Cachexia affects many cancer patients causing weight loss and increasing mortality. Here, the authors identify extracellular Hsp70 and Hsp90, either in soluble form or secreted as part of exosomes from tumor cells, to be responsible for tumor induction of cachexia.